The Singapore Method: a reflection on the teaching-learning process of mathematics - Turizo Martínez, Luis Gabriel; Carreño Colina, Carlos Alejandro; Crissien Borrero, Tito José (Corporación Universitaria Americana, 2019)
This bibliographic review article highlights the concepts of learning, skills and didactics of mathematics under the approach of the Singapore Method for teaching this area. Subsequently, the review is guided under the guidelines established by the Singapore Ministry of Education for the teaching of mathematics, referring to three of the five edges proposed in the Singapore Pentagon, which are: metacognition, mathematical skills and motivation to the student, as outstanding concepts in comparison to what is proposed by the Colombian educational system for the teaching of mathematics f rom the curricular guidelines.In the same way, this review is complemented with many references that help to make some comments that facilitate the understanding of the didactic strategy in the teaching of mathematics De igual manera se complementa esta revisio?n con muchas referencias que coadyuvan a realizar unos comentarios que facilitan mejor la compresio?n de estrategia dida?ctica en la ensen?anza de la matema?tica. Palabras Clave: ensen?anza-aprendizaje, competencias matema?ticas y dida?ctica de las matema?ticas, Me?todo Singapur. Abstract This bibliographic review article highlights the concepts of learning, skills and didactics of mathematics under the approach of the Singapore Method for teaching this area. Subsequently, the review is guided under the guidelines established by the Singapore Ministry of Education for the teaching of mathematics, referring to three of the five edges proposed in the Singapore Pentagon, which are: metacognition, mathematical skills and motivation to the student, as outstanding concepts in comparison to what is proposed by the Colombian educational system for the teaching of mathematics from the curricular guidelines. In the same way, this review is complemented with many references that help to make some comments that facilitate the understanding of the didactic strategy in the teaching of mathematics. Keywords: teaching-learning, mathematical skills and mathematics teaching, Singapore Method.